Pengaruh Kecerdasan Logis Matematis dan Kecerdasan Spasial Terhadap Hasil Belajar Matematika Materi Bangun Ruang - Lya Diah Pramesti, Santika; Oktalia, Anisah (Indonesian Journal of Islamic Elementary Education, 2021)
Learning is influenced by internal and environmental factors. From within, one of them is intelligence. According to Howard Gardner, intelligence includes mathematical logical intelligence and spatial intelligence. Mathematical logical intelligence deals with problem solving. Meanwhile, spatial intelligence is concerned with visualizing diagrams or tables. The purpose of this study was to 1) describe the level of mathematical logical intelligence and the level of spatial intelligence as well as the learning outcomes of mathematics learning materials for students in class V MIS Pakumbulan 2) to analyze the effect of mathematical logical intelligence on student learning outcomes in class V MIS Pakumbulan 3) to analyze the effect of spatial intelligence on theresults class V MIS Pakumbulan student learning 4) to analyze the influence of mathematical logical intelligence and spatial intelligence on the mathematics learning outcomes of class V MIS Pakumbulan students. This type of research is field research witha quantitative approach. Data collection techniques in the form of observation methods, questionnaires and documentation using simple and multiple linear regression data analysis. The results showed that mathematical logical intelligence was quite good, while spatial intelligence was not good enough. In simple regression analysis mathematical logical intelligence is Sig. 0.623> 0.05 and the spatial intelligence Sig. 0.164> 0.05 so there is no partial effect. In multiple analysis the Sig. 0.258> 0.05 so that mathematical logical intelligence and spatial intelligence simultaneously have no effect on mathematics learning outcomes.